Sintering effects on physical properties of bovine hydroxyapatite (BHA)-Al2O3-commercial inert glass (CIG) ternary composites - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2012)
Bovine bone derived hydroxyapatite powders were doped by Al2O3 (15%) and CIG (10%) powders. At the four sintering temperatures (1000-1100-1200-1300°C) and two different sintering times (2-4 hours), mechanical properties of (BHA)-Al2O3-CIG composites were investigated. Density, porosity, % shrinkage rates, hardness and compression strengths of composites were determined. Experimental results show that mechanical properties of composites increase with ascending temperatures until 1200°C and then rapidly decrease due to over-sintering for sintered at 1300°C. Best mechanical properties were obtained for sintered at 1200°C for 2h.